Disorders of Pitch Production in Tone Deafness - Dalla Bella, Simone; Berkowska, Magdalena; Sowinski, Jakub (Frontiers in Psychology, 2011)
Singing is as natural as speaking for the majority of people. Yet some individuals (i.e., 10-15%) are inaccurate singers, typically performing or imitating pitches and melodies inaccurately. This condition, commonly referred to as “tone deafness,“ has been observed both in the presence and absence of deficient pitch perception. In this article we review the existing literature concerning normal singing, poor-pitch singing, and, briefly, the sources of this condition. Considering that pitch plays a prominent role in the structure of both music and speech we also focus on the possibility that pitch production (or imitation) is similarly impaired in poor-pitch singers. Preliminary evidence from our laboratory on poor-pitch singing suggests that pitch imitation may be selectively inaccurate in the music domain without being affected in speech. This finding points to separability of mechanisms subserving pitch production in music and language.